2011
DOI: 10.1097/igc.0b013e31821a3726
|View full text |Cite
|
Sign up to set email alerts
|

Human Epididymis Protein 4 (HE4) as a Serum Tumor Biomarker in Patients With Ovarian Carcinoma

Abstract: Human epididymis protein 4 used in conjunction with CA 125 yields improved specificity for ovarian cancer compared with the use of CA 125 alone, generally similar to results seen in non-Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 17 publications
0
48
1
Order By: Relevance
“…This limit of detection was more than sufficient for analysis of HE4 in serum where normal values of HE4 are considered to be less than 150 pM. 26 This detection limit is a little better than that obtained using the ELISA method for HE4 (15 pM). Therefore, the LSPR biosensor had good analytical performance for the detection of HE4, and was comparable with ELISA.…”
Section: Results and Discussion Lspr Response To Immobilization Processmentioning
confidence: 99%
“…This limit of detection was more than sufficient for analysis of HE4 in serum where normal values of HE4 are considered to be less than 150 pM. 26 This detection limit is a little better than that obtained using the ELISA method for HE4 (15 pM). Therefore, the LSPR biosensor had good analytical performance for the detection of HE4, and was comparable with ELISA.…”
Section: Results and Discussion Lspr Response To Immobilization Processmentioning
confidence: 99%
“…The standard cutoff value of HE4 at 70 pmol/L was determined based on a study by Moore et al (2008) and a recommendation from insert KIT ARCHITECT HE4 reagent that was used in this research. Chang et al, (2011) reported that along with the increase of the cutoff value of either CA125 or HE4, a higher specificity will be obtained; where their cutoff value of CA125 and HE4 on 95% specificity was 127.2 u/ mL and 102.6 pmol/L, respectively. Furthermore, at 98% specificity, the obtained cutoff value was 325.5 u/mL for CA125 and 150.2 pmol/L for HE4.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Moore at al (2008), Huhtinen at al (2009), Nolen et al (2010), Holcomb et al (2011), andChang et al (2011), combined the use of CA125 and HE4 stated that a combination of CA125 and HE4 to further improve the diagnostic capability to differentiate malignant and benign tumors among patients with adnexal masses before surgery. Moore et al (2009) introduced a new algorithm known as ROMA (Risk of Ovarian Malignancy Algorithm) to predict ovarian malignancy, by combining the results of CA125 and HE4 using mathematical calculations (Moore, 2008;2009;Huhtinen, 2009;Nolen, 2010;Chang, 2011;Holcomb, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between serum and PF CA125 has been previously demonstrated (25). Human epididymis protein 4 (HE4), a small glycoprotein and protease inhibitor first identified in epididymal epithelium, has been identified as an ovarian cancer marker, particularly for the serous and endometrioid type (30), and is superior to CA125 (31) either on its own or in combination with CA125 as defined by a higher detection rate (32)(33)(34). The increased specificity of HE4 over CA125 was previously confirmed in a large patient cohort with benign diseases (35).…”
Section: Introductionmentioning
confidence: 99%